Effective Tobacco Control in Washington State: A Smart Investment for Healthy Futures - Julia A. Dilley, MES; Kristen Rohde, MA; Clyde Dent, PhD; Michael J. Boysun, MPH; Michael J. Stark, PhD; Terry Reid, MSW (Centers for Disease Control and Prevention, 2007)
Background Tobacco use remains the leading cause of preventable death in the United States. Following the 1998 Master Settlement Agreement with the tobacco industry, Washington State dedicated substantial funding to the creation of a statewide, comprehensive tobacco control program. This report documents the history and observed effectiveness of that program.Context In 2000, the Washington legislature allocated $100 million out of the first Master Settlement payment of $320 million to tobacco control. The comprehensive tobacco control program was launched late that same year with an annual budget of $15 million.Methods We used existing data from state and national health behavior surveillance systems to describe smoking prevalence among adults and youth. For adult measures, we used data from the Washington State Behavioral Risk Factor Surveillance System and the National Health Interview Survey. For youth measures, we used data from the Washington State Healthy Youth Survey and the national Monitoring the Future survey. We used the National Cancer Institute's "Joinpoint" software to compare trends.Consequences Between 1990 and 2001, adult smoking prevalence in Washington was nearly unchanged, as it was in the United States as a whole. However, from 2001, one year after Washington instituted its comprehensive tobacco control program, to 2005, the prevalence of smoking among adults in Washington declined significantly from 22.5% to 17.6%, and by a significantly larger amount than it did nationally during the same period (22.7% to 20.9%). In addition, the prevalence of youth smoking also declined faster in Washington than it did nationally; for example, from 2000 to 2004, smoking prevalence among 8th graders declined from 12.5% in 2000 to 7.8% in 2004 in Washington but only from 12.2% in to 9.3% nationally.Interpretation Significant reductions in smoking prevalence among Washington residents following the implementation of a comprehensive tobacco control program funded at a level near that recommended by the Centers for Disease Control and Prevention indicate that tobacco control programs are an effective investment for states committed to improving public health.